2023
DOI: 10.1007/s11069-023-06033-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of public emotion on flood disasters in southern China in 2020 based on social media data

Abstract: The exploding popularity of social networks, provides a new opportunity to study disasters and public emotion. Among the social networks, Weibo is one of the largest microblogging services in China. Taking Guangdong and Guangxi in the south of China as a case, Web Scraper was used to obtain Weibo texts related to oods in 2020. The spatial distribution of oods was analyzed using Kernel Density Estimation.Public emotion was analyzed using Natural Language Processing (NLP) tools. The association between oods and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The annual average temperature is 22.5°C, and the annual average precipitation is 1806 mm (Qiu et al, 2021). Studies indicate that Guangxi experienced flood disasters caused by heavy rainfall frequently (Li et al, 2023;Ma et al, 2023a). Qin et al (2021) observed an increase in flood hazards in Guangxi since the 1990s and predicted that future precipitation in the region tends to To further examine the spatial characteristics of historical flood events in China, an analysis was conducted on the distribution across various basin divisions and climate zones, using the Theil-Sen estimator for robust trend detection.…”
Section: Spatial Distribution Of Flood Eventsmentioning
confidence: 99%
“…The annual average temperature is 22.5°C, and the annual average precipitation is 1806 mm (Qiu et al, 2021). Studies indicate that Guangxi experienced flood disasters caused by heavy rainfall frequently (Li et al, 2023;Ma et al, 2023a). Qin et al (2021) observed an increase in flood hazards in Guangxi since the 1990s and predicted that future precipitation in the region tends to To further examine the spatial characteristics of historical flood events in China, an analysis was conducted on the distribution across various basin divisions and climate zones, using the Theil-Sen estimator for robust trend detection.…”
Section: Spatial Distribution Of Flood Eventsmentioning
confidence: 99%